Burnout in healthcare: the case for organisational change. (30th July 2019) - Montgomery, A; Panagopoulou, E; Esmail, A; Richards, T; Maslach, C
Abstract : Burnout is an occupational phenomenon and we need to look beyond the individual to find effective solutions, argue A Montgomery and colleagues